PRAGMATIC FUNCTIONS OF PRESUPPOSITIONS: HOW PRESUPPOSITIONS SHAPE MEANING IN SPOKEN AND WRITTEN LANGUAGE - Eragamreddy, Nagamurali (Premise: Journal of English Education and Applied Linguistics, 2025)
This research examines how presupposition triggers a function in storytelling and debate genres to create meaning, finding that distributions of triggers and contexts of discourse determine interpretive dynamics together. The study confirms that definite descriptions make background assumptions in Arthur Conan Doyle's A Scandal in Bohemia and a free-speech debate transcript, and genre-conventional patterns result—narrative uses low-frequency-high-impact clefts and factices to regulate reader involvement, and debate uses plentiful contrastive ("but") and modal ("may") initiators to regulate contestable premises. With a convergent-parallel mixed-methods design, the study gathered and cleaned the entire text of the short story and verbatim debate transcript. Discourse analysis was used to identify and thematically code presupposition triggers, and automated scripts to count their frequency. Key results indicate that definite appear in 100% of narrative turns and 85% of argument turns, whereas "but" and "may" appear in 23% and 15% of argument turns but fewer than 1% in the narrative. The findings directly speak to the congruity between qualitative patterns (world-construction vs. argumentative setup) and quantitative trends. The research concludes that presuppositions are genre-sensitive tools: semantic triggers ground narratives, while pragmatic triggers propel debate dynamics. Consequences reach as far as dynamic semantics theory, high-level discourse pedagogy, and improved NLP models for presupposition detection.